KATA SAPAAN KEKERABATAN DALAM MASYARAKAT LAMPUNG SUNGKAI - Windo Dicky Irawan (Universitas Muhammadiyah Kotabumi, 2019)
This article was written to (1) describe the form and use of greeting expression based on lineages in the Lampung Ketapang community, South Sungkai Village,Kotabumi, North Lampung, (2) describe the form and use of greeting expression based on lineages in the Lampung Ketapang community, Sungkai Selatan Village, Kotabumi, North Lampung. The data in this study consisted of expression of greeting based on lineage in the Lampung community in Ketapang, South Sungkai Subdistrict, Kotabumi, North Lampung. Data has been collected using proficient methods with fishing techniques. The findings of this study are (1) the form and use of greeting expression based on lineages and based on marital lines.